2014
DOI: 10.5194/amt-7-2981-2014
|View full text |Cite
|
Sign up to set email alerts
|

Overview: Tropospheric profiling: state of the art and future challenges – introduction to the AMT special issue

Abstract: Abstract. This paper introduces the Atmospheric Measurement Techniques special issue on tropospheric profiling, which was conceived to host full papers presenting the results shown at the 9th International Symposium on Tropospheric Profiling (ISTP9). ISTP9 was held in L'Aquila (Italy) from 3 to 7 September 2012, bringing together 150 scientists representing of 28 countries and 3 continents. The tropospheric profiling special issue collects the highlights of ISTP9, reporting recent advances and future challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The microwave measurements (retrievals) of the profiles of the main atmospheric characteristics and trace gas concentrations at various altitudes are used for studying a plethora of atmospheric processes. At the tropospheric altitudes, ground-based measurements of temperature and water-vapor profiles, liquid-water path and other characteristics are widely employed for developing new methods of forecasting weather and hazardous meteorological phenomena [1][2][3][4][5][6][7]. High temporal resolution and acceptable vertical resolution of ground-based passive microwave spectroradiometers allow them to be used in nowcasting.…”
Section: Introductionmentioning
confidence: 99%
“…The microwave measurements (retrievals) of the profiles of the main atmospheric characteristics and trace gas concentrations at various altitudes are used for studying a plethora of atmospheric processes. At the tropospheric altitudes, ground-based measurements of temperature and water-vapor profiles, liquid-water path and other characteristics are widely employed for developing new methods of forecasting weather and hazardous meteorological phenomena [1][2][3][4][5][6][7]. High temporal resolution and acceptable vertical resolution of ground-based passive microwave spectroradiometers allow them to be used in nowcasting.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most promising candidates to feed the weather forecast models is passive microwave remote sensing. For the last~2 decades, ground-based microwave radiometers (GBMRs) [3][4][5][6][7] and their data have been tested for many purposes of operational meteorology and nowcasting, for example, in airports and for meteorological support of major international events [8][9][10]. These devices measure the spectra of the downwelling atmospheric radiation (brightness temperatures) in the range from 20 to 60 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…GMWR measurements were beneficial in studying several atmospheric processes and improving the predictability of NWP models. For example, over the last two decades, this was used in severe weather prediction and deriving the diurnal variability of atmospheric stability indices [10], boundary layer studies [11][12][13], understanding cloud properties [14], and lightening studies [7,8]. In addition, Kadygrov et al (2013) reported that GMMR is preferable over the other existing methods for studying complex processes such as turbulence fluctuation and changes in heat transfer rate in the atmospheric boundary layer during a solar eclipse [15].…”
Section: Introductionmentioning
confidence: 99%